المركز القانوني للوسيط القضائي فيالتشريع الجزائري - سوالم, سفيان (revue mofakir, 2018)
Judicial mediation is conducted by a neutral person called a mediator appointed by the judge after the express consent of the conflict parties in order to seek an amicable solution between them through dialogue and rapprochement of views. Therefore we decided in this research to clarify the legal status of the judicial mediator within the Civil and administrative procedure code,No. 08/09 of 25 February 2008, and Executive Decree, No. 09/100 of 10 March 2009, which sets out modalities for the appointment of the mediator , conditions of appointment and his role as well as judicial supervision of his acts.